2023
DOI: 10.1007/s11250-023-03796-w
|View full text |Cite
|
Sign up to set email alerts
|

Gallibacterium anatis infection in poultry: a comprehensive review

Wafaa A. Abd El-Ghany,
Abdelazeem M. Algammal,
Helal F. Hetta
et al.

Abstract: Gallibacterium anatis (G. anatis), a member of the Pasteurellaceae family, normally inhabits the upper respiratory and lower genital tracts of poultry. However, under certain circumstances of immunosuppression, co-infection (especially with Escherichia coli or Mycoplasma), or various stressors, G. anatis caused respiratory, reproductive, and systemic diseases. Infection with G. anatis has emerged in different countries worldwide. The bacterium affects mainly chickens; however, other species of domestic and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…Gallibacterium anatis , a member of the Pasteurellaceae family [ 1 ], is widely recognized as an inhabitant of the respiratory, intestinal, and genital tracts, playing an important role as an opportunistic pathogen in poultry. Its significance in poultry has recently been comprehensively reviewed [ 2 , 3 ]. While G. anatis is infrequently isolated and characterized as an opportunistic pathogen in mammals, particularly in cattle [ 1 , 4 , 5 , 6 , 7 , 8 ], it has also been found in a range of human cases including chronic bronchitis [ 9 ], lung abscess [ 10 ], bacteremia leading to death in an immunocompromised patient [ 11 ], and cases of diarrhea [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallibacterium anatis , a member of the Pasteurellaceae family [ 1 ], is widely recognized as an inhabitant of the respiratory, intestinal, and genital tracts, playing an important role as an opportunistic pathogen in poultry. Its significance in poultry has recently been comprehensively reviewed [ 2 , 3 ]. While G. anatis is infrequently isolated and characterized as an opportunistic pathogen in mammals, particularly in cattle [ 1 , 4 , 5 , 6 , 7 , 8 ], it has also been found in a range of human cases including chronic bronchitis [ 9 ], lung abscess [ 10 ], bacteremia leading to death in an immunocompromised patient [ 11 ], and cases of diarrhea [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In early references, the tissue origin of G. anatis isolates in cattle was unknown [ 3 , 4 , 5 ]. However, recent studies have indicated that the isolates originate from the respiratory system [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%